VIEWS OF UZBEK AND FOREIGN SCHOLARS ON THE WORKS OF ABDURAUF FITRAT - Usmonov Giyosiddin Murotjonovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the attitude and analysis of Uzbek and foreign scholars to the works of Abdurauf Fitrat, one of the representatives of the literature of the XX century, especially the brilliant representative of Jadid literature, who translated the works of our writers into English, German, French and other languages.